The aneurism of intracranial part of internal carotid artery differential treatment - Zorin, N. A.; Cherednichenko, Yu. V.; Grygoruk, S. P.; Miroshnichenko, A. Yu. (Ukrainian Neurosurgical Journal, 2005)
An experience of surgical treatment of 141 aneurism (at 138 patients) of internal carotid artery intracranial area with the use of itranscranial microsurgical and endovascular methods is presented. Principles of treatment methods choice in dependence on localization, anatomic correlations, clinical course of aneurism are given.